449 Repeated back pain and routes of exit out of paid employment among british civil servants: a follow-up study 1985–2013. (24th April 2018) - Lallukka, T; Mänty, M; Cooper, C; Fleischmann, M; Kouvonen, A; Head, J; Halonen, JI
Abstract : Introduction: Pain is a risk factor for work disability, however, routes of exit out of paid employment among those with chronic pain have not been examined in detail. We aimed to examine the contribution of chronic back pain to subsequent transitions out of paid employment, accounting for covariates. Methods: We included participants of the Whitehall II study cohort (n=8445, 69% men, aged 35–55 at baseline), with measurements of back pain between phases 1 and 3 (1985–1994). Exit from paid employment (health-related, retirement not related to health, unemployment, other) was observed between 1995–2013 (phases 4–11). Those remaining in paid employment served as the reference group. Sex, age, parental and own socioeconomic position, job demands, job control, and body mass index were controlled for. Repeated measures logistic regression models were fitted. Result: Altogether 10% of the participants exited paid employment due to health-related reasons, 2% due to unemployment and further 6.5% due to other reasons. After full adjustments, reporting back pain at one time point (26%) was unassociated with exit due to health reasons, whereas reporting repeated pain (18%) was associated with such exit (OR 1.53, 95% CI: 1.17 to 2.00), when compared to those who did not report pain during phases 1–3 (56%). Associations were somewhat stronger among middle or lower class employees, and non-existent among high class employees. Otherwise differences e.g. by age, working conditions or obesity were small. The risk of exit due to other routes than health-related did not vary between participants with or without pain. Discussion: These results highlight the need for early detection of chronic pain to prevent the risk of health-related early exit out of paid employment. The results further emphasise the importance of identification of high risk groups and their modifiable risk factors, such as adverse working conditions